2019
DOI: 10.1093/botlinnean/boz074
|View full text |Cite
|
Sign up to set email alerts
|

Comparative leaf blade anatomy and micromorphology in the systematics and phylogeny of Bambusoideae (Poaceae: Poales)

Abstract: Leaf blade anatomical and micromorphological data have increasingly proved to be useful in the systematics and phylogeny of Bambusoideae. The presence of well-developed, asymmetrically strongly infolded mesophyll cells (arm cells) as seen in cross-section is regarded a synapomorphy for bamboos, whereas many well-known, widely used features for diagnosing groups remain to be formally tested in a comprehensive phylogenetic framework. In this review, we investigate the use of anatomical and micromorphological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 96 publications
1
8
0
6
Order By: Relevance
“…The leaf blade epidermis of B. bambusoides is consistent with other members of Olyreae and indeed the whole subfamily, considering both long and short cells, in addition to the rows of bulliform cells in the adaxial intercostal zones (Vieira et al 2002;Oliveira et al 2008a, b;Jesus Junior et al 2012;Leandro et al 2016Leandro et al , 2020Lima et al 2020). The short cells observed include silica or cork ones, paired with each other or the lat- ter paired with the basal cells of trichomes, as is common to Poaceae (Calderón and Soderstrom 1973;Soderstrom and Ellis 1988;Vieira et al 2002;Lima et al 2020).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The leaf blade epidermis of B. bambusoides is consistent with other members of Olyreae and indeed the whole subfamily, considering both long and short cells, in addition to the rows of bulliform cells in the adaxial intercostal zones (Vieira et al 2002;Oliveira et al 2008a, b;Jesus Junior et al 2012;Leandro et al 2016Leandro et al , 2020Lima et al 2020). The short cells observed include silica or cork ones, paired with each other or the lat- ter paired with the basal cells of trichomes, as is common to Poaceae (Calderón and Soderstrom 1973;Soderstrom and Ellis 1988;Vieira et al 2002;Lima et al 2020).…”
Section: Discussionsupporting
confidence: 71%
“…The stomatal complexes with dome-shaped subsidiary cells of B. bambusoides are very common in Bambusoideae ( Metcalfe 1960 ; Ellis 1979 ; Zuloaga et al 1993 ; Oliveira et al 2008a , b ; Jesus et al 2012; Ferreira et al 2013 ; Leandro et al 2016 , 2020 ; Lima et al 2020 ), occurring in well-defined rows in the intercostal zones on either side of a costal zone. Although papillae on the subsidiary cells have been documented for some Olyreae , mainly members of subtribe Olyrinae ( Lima et al 2020 ), and are also characteristic of Chusqueinae ( Clark 1986 ; Soderstrom and Ellis 1987 ; Fisher et al 2009 , 2014 ), these are here indicated as absent in Buergersiochloa .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, los estudios anatómicos y morfológicos de las hojas de follaje (de las ramificaciones) de las diferentes especies de bambúes son menos frecuentes. Existen trabajos que mencionan los caracteres de la superficie foliar, como la presencia de tricomas, papilas, células silíceas y células fusoides, que contribuyen a la diferenciación de las entidades (Ghosh & Negi, 1959;Tateoka, et al 1959;Metcalfe, 1960;Grosser & Liese, 1971;Guerreiro et al, 2016;Leandro et al, 2016Leandro et al, , 2017Leandro et al, , 2018Leandro et al, , 2020Alegría Olivera et al, 2017). Varios autores informan que las características anatómicas y micromorfológicas de las hojas de follaje son útiles para la definición y delimitación de taxones en la subfamilia Bambudoideae, sus tribus y subtribus (Márquez et al, 2011;Leandro et al, 2016Leandro et al, , 2017Leandro et al, , 2020Alegría Olivera et al, 2017).…”
Section: Introductionunclassified